Peran dan Strategi Bank Sampah dalam Mengurangi Volume Sampah Rumah Tangga Perspektif Maqashid Syariah (Studi pada Bank Sampah Induk Surabaya) - alfi khoirin nisa; Muhammad Yazid (JES (Jurnal Ekonomi Syariah), 2026)
This study aims to determine the role and strategies of Bank Sampah Induk Surabaya in reducing household waste volume from the perspective of maqashid sharia. Proper waste management has an important influence on the environment and community life. This study used a qualitative approach through observation and interviews conducted at Bank Sampah Induk Surabaya in April 2026. The results showed that Bank Sampah Induk Surabaya acts as a facilitator, waste manager, and increases public awareness regarding waste management through educational activities. The strategies implemented include allowing customers to become waste-saving members at BSIS, providing waste collection services, supporting facility loans, organizing training events for the community, strengthening institutional and administrative management through handicraft sales, and establishing cooperation with partners. From the perspective of magashid sharia, these efforts are in accordance with the purpose of Islam in creating public welfare for society and the environment.